Influence of Microplastics on the Mobility, Bioavailability, and Toxicity of Heavy Metals: A Review - Liu, Guangxia; Dave, Preeti H.; Kwong, Raymond W. M.; Wu, Mengjie; Zhong, Huan (Bulletin of environmental contamination and toxicology, 2021)
Microplastics (MPs) can pose ecological risk to the environment and have the potential to negatively affect human health, raising serious public concerns. It is recognized that MPs could act as a vector for various environmental pollutants including heavy metals and potentially influencing their mobility, fate, and bioavailabilty in the environment. However, knowledge on the mechanisms underpinning the interaction processes between MPs and heavy metals is far from clear. This review discusses the effects of MPs on the adsorption/desorption, speciation and bioavailability, and toxicity of various heavy metals. The present review also systematically identifies the environmental factors (e.g., pH, ionic strength, and organic matters) that could affect their interaction processes. This work aims to establish a meaningful perspective for a comprehensive understanding of the indirect ecological risks of MPs as vectors for contaminants. The work also provides a reference for the development of better regulatory strategies in mitigating the negative effects caused by the co-existence of MPs and heavy metals.